OPTIMIZING THE PERFORMANCE OF YOUNG ENTREPRENEURIAL MSMES (STUDEPRENEURS) THROUGH INCREASING ENTREPRENEURIAL COMPETENCE - Sari, Wiendy Puspita; Sari, Puteri Andika (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
Indonesia is one of developing countries that has been severely affected by Covid-19, especially in economics. This causes Businesses in Indonesia to sluggish, especially micro, small, and medium enterprises (MSME’s). Audience of this activity is community of young entrepreneurs called Studepreneur. Studepreneur consist of college students who have business in varous sectors, such as culinary, fashion, plant cultivation, fish cultivation, etc. Initially Studepreneurs were entrepreneurship to fill their spare time, but during this pandemic this entrepreneurial activity also supports the cost of living, especially the education fee. Lack of entreperenurial competences is a challenge for Studepreneurs to maintain and improve their business performance during pandemic. The purpose of this service activity is to give knowledge and insight of entrepreneurial competencies to support their business sustainability. The method used in this cativity is training dan interactive discussion. 11 member of Studepreneurs are join this training. Pre test and Post Test are used to evaluate the training. The evaluation results show that 100% audience more understand entrepreneurial competencies after the training.